PELAYANAN PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA BATU AMPAR KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR TAHUN 2018 - Atik Yuliana; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was motivated by the selection of PAMSIMAS target villages in Batu Ampar Village in 2012 in accordance with the Decree of the Minister of Public Works of the Republic of Indonesia Number: 79 / KTPS / DC / 2013 concerning the Determination of Target Districts / Cities for Community-Based Water Supply and Sanitation Programs. The implementation of the Pamsimas program at the district level is carried out by BAPPEDA, the Health Office and the Public Works Cipta Karya which are members of the Indragiri Hilir Regency AMPL POKJA in accordance with Indragiri Hilir Regent Regulation No. Indragiri Hilir Regent Regulation No. 9/2016 on Regional Policies and Strategies for the Development of Drinking Water Supply Systems was also issued. The implementation of the Pamsimas program at the village level is carried out by the Village Government, KKM, SATLAK, and BPSPAMS which are assisted by the Community Facilitator Team. As for the formulation of the problem in this research is How Community-Based Drinking Water and Sanitation Services (PAMSIMAS) in Batu Ampar Village, Kemuning District, Indragiri Hilir Regency in 2018. This research was conducted with the aim of describing Community Based Water Supply and Sanitation Services (PAMSIMAS) in Batu Ampar Village, Kemuning District, Indragiri Hilir Regency in 2018. This research is a descriptive study with a qualitative approach. The location of this research was conducted in Batu Ampar Village. The data collection techniques used were interviews and documentation. The data analysis technique used is descriptive and qualitative methods. The results of this study indicate that the PAMSIMAS program services in Batu Ampar Village have not run optimally, BPSPAMS which is responsible for the operational and maintenance stages does not carry out its responsibility for the duties assigned to maintain PAMSIMAS assets, this can be seen from the unmet need for clean water to the community because inadequate machines, not only the problem of a shortage of clean water supply which becomes an obstacle in service but also the damage to the pipeline network which causes clean water services to the community to be cut off, then the problem of many public faucets that do not work. Keywords: Transparency, Accountability, Conditional, Participatory, Equal Rights.